Komposisi dan Keanekaragaman Tumbuhan Rawa Air Tawar Musiman Kasiono Oe Kecamatan Lawa Kabupaten Muna Barat Sulawesi Tenggara (University of Halu Oleo, 2023)
This reserch purpose is to determine the composition and diversity of seasonal freshwater swamp plant growth of Kasiono Oe, Lawa District, West Muna Regency, Southeast Sulawesi and to determine environmental factors that affect the growth of seasonal freshwater swamp plant Kasiono Oe, Lawa District, West Muna Regency, Southeast Sulawesi.This research is a descriptive-quantitative research conducted at 5 stations in the swamp area, namely station I (Lianoghule river flow), station II (Mata river flow), station III (Soni river flow), station IV (close to settlements) and station V (near residential area). with plantations). Determination of the location using the line method and plotted lines, the determination of the line method with a width of 20x20 (for the tree phase) and the line method (for the seedling, sapling and tihang phases) installation of a 50 m transect with a length of 100 m.The results showed that the composition of plant species found in station I was found 4 plant species totaling 115 individuals, station II found 9 plant species totaling 71 individuals, station III found 5 plant species totaling 49 individuals, station IV found 5 plant species totaling 61 individuals and station IV found 8 plant species totaling 109 individuals. The diversity index for tree strata was 1.03, tihang strata 0.63, sapling strata 1.3 and seedling strata at station II 1.09 and station V 1.01. The highest uniformity index for the tree strata was 0.943 and the lowest was 0.918, for the tihang strata 0.91, the highest sapling was 0.97 and the lowest was 0.81 and the seedling strata had the highest 0.Keywords: Composition of plant species, diversity, Seasonal freshwater swamp.